2011
DOI: 10.1115/1.4005222
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Sensor Concept for Optimization of Loosening Diagnostics in Total Hip Replacement

Abstract: The main reason for the revision of total hip replacements is aseptic loosening, caused by stress shielding and wear particle induced osteolysis. In order to detect an implant loosening early, the osseointegration of endoprosthetic implants must be measured exactly. Currently applied diagnostic methods, such as standard radiographs and clinical symptomatology, often result in an imprecise diagnosis. A novel radiation-free method to improve the diagnostic investigation of implant loosening is presented. The oss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 17 publications
0
22
0
1
Order By: Relevance
“…Most THR stability assessment studies have focused on the femoral component [20][21][22][23][24][35][36][37][38][39][40][41][42]. Vibration analysis studies on acetabular loosening are limited because the acetabulum has a complex geometry compared to the femur and has a thicker overlaying soft tissue layer, which acts as a signal buffer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most THR stability assessment studies have focused on the femoral component [20][21][22][23][24][35][36][37][38][39][40][41][42]. Vibration analysis studies on acetabular loosening are limited because the acetabulum has a complex geometry compared to the femur and has a thicker overlaying soft tissue layer, which acts as a signal buffer.…”
Section: Discussionmentioning
confidence: 99%
“…Georgiou and Cunningham [23] also compared vibration analysis with standard radiological assessment and demonstrated that vibration analysis improved diagnostic precision by 20%; moreover, they were able to detect 13% more cases than radiological diagnosis with 81% sensitivity and 89% specificity. Other research groups have used vibration analysis for different orthopaedic applications such as; the telemetry technique to assess THR femoral loosening [24][25][26], trans-femoral osseointegration [27][28][29], intra-operative initial implant stability [6,[30][31][32][33], THR femoral stability utilising acoustic resonance responses [7,[34][35][36][37][38][39][40][41], and complete THR component loosening (femoral and acetabular) [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mentioned studies used either an impact hammer or an electro-magnetic shaker without one method gaining unreserved approval [19]. Only one research group worked on an alternative approach combining excitation and measurement [20,21]. They aimed for an actuator-sensory-element, which is intended to be implemented into the prosthesis itself.…”
Section: Introductionmentioning
confidence: 99%
“…Information concerning mechanical stress of bone cement and hip-joint small dislocations monitoring are fundamental to promote high durability of the prosthesis, comfort and reliability to the patient. In this sense strong efforts are being done in order to develop sensors for the measurement of cement-prostheses interface forces based on different transducers and geometries [5][6][7][8][9][10], but the issue is far from being solved for practical situations.…”
Section: Introductionmentioning
confidence: 99%